The Cambridge handbook of communication disorders - Cummings, Louise (Cambridge : Cambridge University Press, 2014)
"Many children and adults experience impairment of their communication skills. These communication disorders impact adversely on all aspects of these individuals' lives. In thirty dedicated chapters, The Cambridge Handbook of Communication Disorders examines the full range of developmental and acquired communication disorders and provides the most up-to-date and comprehensive guide to the epidemiology, aetiology and clinical features of these disorders. The volume also examines how these disorders are assessed and treated by speech and language therapists and addresses recent theoretical developments in the field. The handbook goes beyond well-known communication disorders to include populations such as children with emotional disturbance, adults with non-Alzheimer dementias and people with personality disorders. Each chapter describes in accessible terms the most recent thinking and research in communication disorders. The volume is an ideal guide for academic researchers, graduate students and professionals in speech and language therapy"--
Includes bibliographical references and index.
Keywords: Communicative disorders -- Handbooks, manuals, etc